Variation in anatomical and morphological properties of juvenile Acacia Mangium according to different height levels - Ibrahim, Nor Hidayah; Abdullah, Noor Hidayu; Mohamed Khaidi, Noor Suhada (2010)
Anatomical properties of Acacia mangium based on three portion of tree which is bottom, middle and top. The tree was obtained from UiTM Pahang Forest Reverse. The nature of pores or vessel is solitary pores seven up to ten in numbers. It also present solitary pore which is medium sized pores. The nature of wood rays is is heterogeneous ray. The tylosis is assist in pore or vessel. This information is fundamental which could assist in proper wood utilization. Fiber morphology of Acacia mangium according to the height level was ascertained. The fiber length, fiber diameter and lumen diameter were determined using digital microscope. Tree does not significant for FL but significance for FD, LD, CWT, RR and FP. Portion does not significant for FD, LD, CWT and RR but significance for fiber length and felting power. The effect interaction of tree and portion is not significance for FL but significance for FD, LD, CWT, RR and FP. Generally, the properties of Acacia mangium are suitable in paper making but not enough strength due to the runkel ratio and felting power according to the height level.